(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
Thracian belongs to the group of languages spoken over the entire period of Antiquity in the areas of south-eastern Europe (mostly the Balkans) and which, like other vernaculars spoken in this and neighbouring areas, had died out by the end of the Roman period leaving but scanty evidence. This chapter provides an introduction into the state of our current knowledge about the Thracian language and epigraphy and the perspectives of research of this language. Since our comprehension and understanding of grammatical system of Thracian is limited, the current knowledge of the language makes any translation of attested inscriptions impossible. It is however expected that the progress in studying development and history of the Greek script may provide us with new and relevant data for interpretation of Thracian.